Market discipline by bank creditors during the 2008–2010 crisis - Bennett, Rosalind L.; Hwa, Vivian; Kwast, Myron L. (Journal of Financial Stability, 2015)
We investigate whether uninsured depositors, insured depositors, and general creditors exhibit evidence of quantity market discipline during the recent financial crisis. To establish which types of creditors expect to incur loss, we evaluate the FDIC's expectations about losses to creditors at banks that failed between 2008 and 2010. Our results show that quantity market discipline tends to begin far enough in advance to signal to both banks and supervisors that corrective actions can and should be taken. Furthermore, creditors are able to distinguish between banks of different risk levels. Our findings support several policy implications for encouraging market discipline.